2023
DOI: 10.1007/s00107-023-01999-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the moisture content on the fracture energy and tensile strength of hardwood spotted gum sawn timber and adhesive bonds (gluelines)

Peiqing Lu,
Benoit P. Gilbert,
Chandan Kumar
et al.

Abstract: This study aims to measure the fracture properties, including crack initiation and propagation, of Australia’s native forest grown spotted gum ([SPG], Corymbia citriodora) sawn timber and associated adhesive bonds at different moisture content levels. The collected data were used as input values to develop a numerical model to understand the delamination of SPG glulam beams when exposed to a wetting and drying process. Thus, Mode I and Mode II fracture energies for crack propagation along radial and glueline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This lack of relationship between shear strength and delamination suggests the glueline failures are caused through a motion other than shear. Lu et al (2024) also concluded this where after conducting fracture energy experiments using bonded SPG specimens. Similar studies on the performance of bonded wood products found complimentary results where CYCLED testing presents a significant decrease in bond performance compared to DRY results (Klausler et al, 2013;Faircloth et al, 2023).…”
Section: Rp Samplesmentioning
confidence: 83%
“…This lack of relationship between shear strength and delamination suggests the glueline failures are caused through a motion other than shear. Lu et al (2024) also concluded this where after conducting fracture energy experiments using bonded SPG specimens. Similar studies on the performance of bonded wood products found complimentary results where CYCLED testing presents a significant decrease in bond performance compared to DRY results (Klausler et al, 2013;Faircloth et al, 2023).…”
Section: Rp Samplesmentioning
confidence: 83%
“…Traditional timber buildings often employ logs as structural members to bear loads. However, this approach overlooks the impact of factors such as moisture content, knots, grain direction, and decay on the strength of wood (Lu et al 2024; Pang et al 2021; Zhang et al 2022a; Zhang et al 2021). These defects often lead to deformations and cracks in wood members (Wang et al 2023).…”
Section: Introductionmentioning
confidence: 99%